Treatment of secondary hyperparathyroidism: the clinical utility of etelcalcetide - Cozzolino M; Galassi A; Conte F; Mangano M; Di Lullo L; Bellasi A (Dove Medical Press, 2017)
Mario Cozzolino,1 Andrea Galassi,1 Ferruccio Conte,1 Michela Mangano,1 Luca Di Lullo,2 Antonio Bellasi1,3 1Department of Health Sciences, Renal Division, University of Milan, ASST Santi Paolo e Carlo, San Paolo Hospital, Milan, 2U.O.C. Nefrologia e Dialisi, Ospedale L. Parodi Delfino, Colleferro, Roma, 3Sant’Anna Hospital, ASST-Lariana, Como, Italy Abstract: Secondary hyperparathyroidism (SHPT), a very frequent, severe, and worsening complication of chronic kidney disease, is characterized by high serum parathyroid hormone (PTH), parathyroid gland hyperplasia, and disturbances in mineral metabolism. Clinically, SHPT shows renal osteodystrophy, vascular calcification, cardiovascular damage, and fatal outcome. Calcium-sensing receptor (CaSR) is the main physiological regulator of PTH secretion; its activation by calcium rapidly inhibits PTH. Another important player in regulating mineral metabolism is vitamin D receptor (VDR), which is under the influence of vitamin D and influences the intestinal absorption of calcium and phosphate, PTH gene expression, and bone calcium mobilization. Serum phosphate levels influence fibroblast growth factor 23 (FGF-23) production, a phosphatonin that modulates serum phosphate reabsorption, PTH synthesis, and vitamin D production. Current therapeutic approaches consist of 1) phosphate intake control by diet or phosphate binders, 2) vitamin D by VDR activation, and 3) calcimimetic agents that activate CaSR. Recently, a new long-acting peptide (etelcalcetide) belonging to the calcimimetics class was approved for intravenous use in hemodialysis patients with SHPT. Etelcalcetide binds directly to CaSR, by a sulfide bond, inhibiting the production and secretion of PTH by parathyroid glands. After intravenous administration in rats, etelcalcetide is quickly distributed to the tissues and eliminated by kidneys, while in uremic animals the nonrenal excretion is only 1.2%. In hemodialysis patients, the treatment itself is the main route of elimination. Etelcalcetide in hemodialysis patients with SHPT was more effective than placebo and cinacalcet, with a PTH reduction of >30% in 76% of patients with etelcalcetide versus 10% with placebo. Particular attention was paid to the safety of the drug; the most common adverse event was asymptomatic blood calcium reduction, similar to cinacalcet, while gastrointestinal symptoms were less frequent. This promising new drug available for better control of SHPT will, together with drugs already in use, optimize the treatment to normalize the biochemical parameters. Keywords: secondary hyperparathyroidism, CKD-MBD, calcimimetic, dialysis